2020
DOI: 10.1126/sciimmunol.aav1080
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 and IL-2 activation of STAT5 is required for optimal IL-22 production in ILC3s during colitis

Abstract: Signal transducer and activator of transcription (STAT) proteins have critical roles in the development and function of immune cells. STAT signaling is often dysregulated in patients with inflammatory bowel disease (IBD), suggesting the importance of STAT regulation during the disease process. Moreover, genetic alterations in STAT3 and STAT5 (e.g., deletions, mutations, and single-nucleotide polymorphisms) are associated with an increased risk for IBD. In this study, we elucidated the precise roles of STAT5 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…We then investigated the mechanisms involved in butyrate induction of IL-22 production. RNA-seq data showed that Ahr, a transcription factor for IL-22 through directly binding to Il22 promoter 14,39,40 , and Hif1a, a transcription factor mediating hypoxia that has been recently shown to regulate IL-22 production in CD4 + T cells 41 , were upregulated in butyratetreated CD4 + T cells (Fig. 4a).…”
Section: Resultsmentioning
confidence: 95%
“…We then investigated the mechanisms involved in butyrate induction of IL-22 production. RNA-seq data showed that Ahr, a transcription factor for IL-22 through directly binding to Il22 promoter 14,39,40 , and Hif1a, a transcription factor mediating hypoxia that has been recently shown to regulate IL-22 production in CD4 + T cells 41 , were upregulated in butyratetreated CD4 + T cells (Fig. 4a).…”
Section: Resultsmentioning
confidence: 95%
“…In addition, UAMC-00050 increased the protein levels of IL-2, IL-10, IL-17 and IL-23 in control mice. This remarkable effect could possibly be explained by the fact that the administration of a protease inhibitor in control mice disturbs the protease/antiprotease balance, resulting in the activation of IL-2 and IL-23 and eventually the activation of IL-22 in order to maintain mucosal integrity ( Bauché et al, 2020 ). Besides, IL-10 and IL-17 have been linked to epithelial proliferation and repair ( Andrews et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The patients with CD have a lower number of functional T regs and IL‐2 levels in their guts. IL‐2 and IL‐23 induce STAT5 activation mediated IL‐22 release by colonic LP ILC3s 166 . Mechanistically, IL‐23 induces a STAT3‐STAT5 complex binding to the IL‐22 promoter DNA elements in ILC3s.…”
Section: Ilcs and Adaptive Immune Cross‐talk During Homeostasismentioning
confidence: 97%
“…Mechanistically, IL‐23 induces a STAT3‐STAT5 complex binding to the IL‐22 promoter DNA elements in ILC3s. Thus, STAT5a/b signaling in gut ILC3s maintains gut epithelial barrier and integrity during pathogen ( Citrobacter rodentium )‐induced colitis 166 . Hence, IL‐2 produced by either CD4 + T cells or ILC3s exerts a protective action during colitis through affecting Tregs and colonic ILC3s.…”
Section: Ilcs and Adaptive Immune Cross‐talk During Homeostasismentioning
confidence: 99%